2020
DOI: 10.1074/mcp.ra119.001823
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation Site Analysis Reveals Sex-related Differences in Protein N-glycosylation in the Rice Brown Planthopper (Nilaparvata lugens)

Abstract: Glycosylation is a common modification of proteins and critical for a wide range of biological processes. Differences in protein glycosylation between sexes have already been observed in humans, nematodes and trematodes, and have recently also been reported in the rice pest insect Nilaparvata lugens. Although protein N-glycosylation in insects is nowadays of high interest because of its potential for exploitation in pest control strategies, the functionality of differential N-glycosylation between sexes is yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…Therefore, improving the catalytic activity, methanol tolerance, and transesterification efficiency of lipase has attracted widespread attention [ 29 ]. At present, structure-based semi-rational design is an effective strategy for improving enzyme performance, which is undertaken by adding modifications to particular positions along the enzyme [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving the catalytic activity, methanol tolerance, and transesterification efficiency of lipase has attracted widespread attention [ 29 ]. At present, structure-based semi-rational design is an effective strategy for improving enzyme performance, which is undertaken by adding modifications to particular positions along the enzyme [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of plant lectins to glycosylated proteins of insects being an important interaction to explain the insecticidal activity of lectins, prompted us to study in more detail the glycosylation in insects and the importance of glycosylation for insect development. Analyses of the N-glycomes from several insects revealed that high-mannose and paucimannose N-glycans are highly abundant, explaining why especially mannose-binding lectins show good interaction with insect glycoconjugates [109][110][111][112]. Recent research also indicated differences in the N-glycan profile for male and female insects of Nilparvata lugens, with male insects containing less high-mannose and more paucimannose type structures compared to the female insects [110,111].…”
Section: Role Of Lectins In Plantsmentioning
confidence: 99%
“…Analyses of the N-glycomes from several insects revealed that high-mannose and paucimannose N-glycans are highly abundant, explaining why especially mannose-binding lectins show good interaction with insect glycoconjugates [109][110][111][112]. Recent research also indicated differences in the N-glycan profile for male and female insects of Nilparvata lugens, with male insects containing less high-mannose and more paucimannose type structures compared to the female insects [110,111]. Both O-and N-glycosylation are important for insect physiology and development, as shown by RNAi experiments.…”
Section: Role Of Lectins In Plantsmentioning
confidence: 99%
“…Hydrophilic enrichment followed by high mass accuracy MS employing complementary fragmentation techniques (higher‐energy collision dissociation and electron transfer dissociation) proved to be an effective method for N‐glycopeptide identification (Zeng et al, 2018). The study of N‐linked glycosylation was recently enhanced using a newly developed method that elegantly combines filter‐aided sample preparation with lectin affinity chromatography (Scheys et al, 2020). Thousands of N‐GlcNAc modified sites have been identified using these enrichment methods, and the functions of these modifications have been interpreted (Bi et al, 2021).…”
Section: Characterizing Ptms and Cell Signalingmentioning
confidence: 99%